(3OQGSGJ YdejI aj GbJUGOjGJ GdQjGVI ddLejY s - (3jMj eMeO(B, (3GdLjhTjs ((3GdbGgQI(B:s (3eQcR GdcJGH ddfTQ(B,s, 2023)
(3fehPL ebJQMNUNUI eTQhYGJ GdQjGVI ddLejY HhRGQI GdTHGH hGdCfOjI GdQjGVjI heQGcR GdTHGH, fehPL ebJQM dJShjb eTQhYGJ GdQjGVI ddLejY, fehPL ebJQM dEOGQI eQGcR GdJfejI GdQjGVjI aj VhA GdEOGQI GdGbJUGOjI HLeghQjI eUQ GdYQHjI, QDjI efgLjI dGSJNOGe GdQjGVI ddLejY ceONd dJMbjb GdJfejI GdeSJOGeI aj GdeLJeY GdeUQj, QDjI eQLYjI dGSJMOGK OHdheI egfjI aj eLGd GdSjGMI GdJQhjMjI HcdjI GdJQHjI GdQjGVjI ddHfjf LGeYI MdhGf, QDjI GSJTQGbjI JWHjbjI(B- (3dGSJMOGK OHdheI egfjI aj GbJUGOjGJ GdJQhjM GdQjGVj HcdjGJ GdJQHjI GdQjGVjI HLeghQjI eUQ GdYQHjI, fehPL JWHjbj ddSjGSGJ GdJfajPjI ddGSJKeGQ GdQjGVj GdeSJOGe aj GdeDSSGJ GdQjGVjI aj VhA bGfhfj GdQjGVI hGdGSJKeGQ, GdHfGA ebjGS ddYhGFO GdGbJUGOjI GdGLJeGYjI hGdHjFjI ddGJMGO GdeUQj GdYGe ddQjGVI ddLejY, GdYhGFO GdGbJUGOjI hGdGLJeGYjI ddQjGVI ddLejY HGdCfOjI GdQjGVjI heQGcR GdTHGH, OQGSI JMdjdjI dYedjGJ GdJTZjd GdOGNdjI hGdcaGAI GdJTZjdjI HGdefTBJ GdJQhjMjI HeMGaXI GdLjRI, ebGdGJ UMajI aj GbJUGOjGJ GdQjGVI hGdJQhjM(B.s
(3GdeQGLY U(B.47(3, (B95(3, (B132(3, (B166(3, (B189(3, (B219(3, (B248(3, (B278(3, (B310(3, (B343.s
Keywords: (3GdJfejI GdEbJUGOjIs; (3GdJfejI GdeSJOGeIs; (3GdQjGVI GdHOfjI(B- (3GdLhGfH GdEbJUGOjIs